Quaternary range and demographic expansion of Liolaemus darwinii (Squamata: Liolaemidae) in the Monte Desert of Central Argentina using Bayesian phylogeography and ecological niche modelling. Issue 15 (20th June 2013) - Camargo, Arley; Werneck, Fernanda P.; Morando, Mariana; Sites, Jack W.; Avila, Luciano J.
Abstract: Until recently, most phylogeographic approaches have been unable to distinguish between demographic and range expansion processes, making it difficult to test for the possibility of range expansion without population growth and vice versa. In this study, we applied a Bayesian phylogeographic approach to reconstruct both demographic and range expansion in the lizard Liolaemus darwinii of the Monte Desert in Central Argentina, during the Late Quaternary. Based on analysis of 14 anonymous nuclear loci and the cytochrome b mitochondrial DNA gene, we detected signals of demographic expansion starting at ~55 ka based on Bayesian Skyline and Skyride Plots. In contrast, Bayesian relaxed models of spatial diffusion suggested that range expansion occurred only between ~95 and 55 ka, and more recently, diffusion rates were very low during demographic expansion. The possibility of population growth without substantial range expansion could account for the shared patterns of demographic expansion during the Last Glacial Maxima (OIS 2 and 4) in fish, small mammals and other lizards of the Monte Desert. We found substantial variation in diffusion rates over time, and very high rates during the range expansion phase, consistent with a rapidly advancing expansion front towards the southeast shown by palaeo‐distribution models. Furthermore, the estimated diffusion rates are congruent with observed dispersal rates of lizards in field conditions and therefore provide additional confidence to the temporal scale of inferred phylogeographic patterns. Our study highlights how the integration of phylogeography with palaeo‐distribution models can shed light on both demographic and range expansion processes and their potential causes.